Nanometric probing with a femtosecond, intra-cavity standing wave - Heldt, Tobias; Oelmann, Jan-Hendrik; Guth, Lennart; Lackmann, Nick; Matt, Lukas; Pfeifer, Thomas; Crespo López-Urrutia, José Ramon (Nanophotonics, 2024)
Optical standing waves are intrinsically nanometric, spatially fixed interference-field patterns. At a commensurate scale, metallic nanotips serve as coherent, atomic-sized electron sources. Here, we explore the localized photofield emission from a tungsten nanotip with a transient standing wave. It is generated within an optical cavity with counter-propagating femtosecond pulses from a near-infrared, 100-MHz frequency comb. Shifting the phase of the standing wave at the tip reveals its nodes and anti-nodes through a strong periodic modulation of the emission current. We find the emission angles to be distinct from those of a traveling wave, and attribute this to the ensuing localization of emission from different crystallographic planes. Supported by a simulation, we find that the angle of maximum field enhancement is controlled by the phase of the standing wave. Intra-cavity nanotip interaction not only provides higher intensities than in free-space propagation, but also allows for structuring the light field even in the transverse direction by selection of high-order cavity modes.